2013
DOI: 10.17503/agrivita-2013-35-1-p044-053
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhiza Fungi as an Indicator of Soil Fertility

Abstract: Arbuscular mycorrhizal fungi (AMF) are ubiquitous organism that forms association with the root of most terrestrial plants. AMF association also influence soil fertility through the enhancement of chemical, biological and physical content. In this study, we enumerated AMF spores from rhizosphere of Tithonia difersivolia as an indicator of soil fertility. The results showed that the most fertile soil had the highest AMF spores density. This research has confirmed that AMF has high interaction with organic carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
8
0
2
Order By: Relevance
“…There was positive correlation between CEC and root infection (r = 0.378, P < 0.05) and spore density (r = 0.307, P < 0.05) (Table 6). This is because mycorrhizae play an active role in the process of organic C decomposition, releasing organic acids to increase soil CEC and the availability of P (Syibli et al, 2013). Leaching of soil nutrients was not easy to occur because of the wider absorption area due to the high content of soil organic colloids (Bruun et al, 2012).…”
Section: Treatmentmentioning
confidence: 99%
“…There was positive correlation between CEC and root infection (r = 0.378, P < 0.05) and spore density (r = 0.307, P < 0.05) (Table 6). This is because mycorrhizae play an active role in the process of organic C decomposition, releasing organic acids to increase soil CEC and the availability of P (Syibli et al, 2013). Leaching of soil nutrients was not easy to occur because of the wider absorption area due to the high content of soil organic colloids (Bruun et al, 2012).…”
Section: Treatmentmentioning
confidence: 99%
“…Syib'li et al (2013) suggested that high abundance of mycorrhiza in field can be used as the phytoremediation of soil fertility, since AM has high interaction with organic material, total phosphorus, and cation exchange capacity.…”
Section: Resultsmentioning
confidence: 99%
“…including soil temperature, soil pH, soil moisture, soil profile, soil texture, slope, carbon organic soil, light intensity, and rainfall, were also measured in the plot (Syarif et al, 2007;Syib'ili et al, 2013).…”
Section: Amf Monitoring Of Root Infectionmentioning
confidence: 99%
“…Leucaena leucocepala, Calliandra calothyrsus, and Gliricidia sepium. The number of spores in the plant rhizosphere, especially the Fabaceae family, can indicate a land's fertility (Syib'ili et al, 2013).…”
Section: Number Of Amf Spores In the Rhizospherementioning
confidence: 99%